Evaluation of alloplastic mandibular reconstruction combined with a radial forearm flap compared with a vastus lateralis myocutaneous flap as the first approach to two-stage rehabilitation in advanced oral cancer. Issue 5 (June 2019) - Gruichev, D.; Yovev, T.; Kniha, K.; Möhlhenrich, S.C.; Goloborodko, E.; Lethaus, B.; Hölzle, F.; Modabber, A.
Abstract: After continuity resection of the mandible, reconstruction of continuity with a reconstruction plate and soft tissue can be an alternative to immediate osseous reconstruction in patients with advanced oral cancer. We evaluated exposure of the plate in such reconstructions by comparing the results of a radial forearm flap (RFF) with a vastus lateralis myocutaneous flap (VLMF). We also analysed the resection margins and the incidence of secondary osseous reconstructions after one year free from relapse. We retrospectively examined all 48 mandibular reconstructions in which a reconstruction plate and RFF or VLMF had been used between 2007 and 2016. Exposure rates of plates were assessed and local (size and site of resection) and systemic risk factors (age, sex, treatment with radiation, and smoking) evaluated. Reconstruction plates, together with a RFF, were significantly more likely to be exposed than those with a VLMF (p = 0.01). There was significantly more exposure in the RFF group in mandibular defects larger than 6 cm, in contrast to the VLMF group (p = 0.002). Younger age (p < 0.001), lower body mass index (BMI) (p = 0.05) and smoking (p = 0.011) led to more exposure. In seven cases a second operation was necessary due to macroscopically invaded or close margins. Thirty-one patients had no bony reconstruction because of local recurrence, distant metastases, inadequate resection margins, poor general condition, or a second (different) tumour. Exposure of the plate after mandibular reconstruction happens less often with the VLM flap than with the RFF. The two-step approach can be an option in the treatment of advanced oral cancer.